Do age, period or cohort effects explain circulatory disease mortality trends, Scotland 1974–2015?. Issue 8 (20th September 2019) - Parkinson, Jane; Minton, Jon; Bouttell, Janet; Lewsey, James; Shah, Anoop; McCartney, Gerry
Abstract : Objective: We aimed to explore whether age, period or cohort effects explain the trends and inequalities in ischaemic heart disease (IHD) and cerebrovascular disease (CeVD) mortality in Scotland. Methods: We analysed IHD and CeVD deaths for 1974–2015 by sex, age and area deprivation, visually explored the data using heatmaps and dotplots and built regression models. Results: CeVD mortality improved steadily over time while IHD mortality improved more rapidly from the late 1980s. Age effects were evident; both outcomes showed an exponential relationship with age for all except males for IHD in the 1980s and 1990s. The mortality profiles by age became older, although improvement was slower for those aged <50 years for IHD, especially for males, and faster for CeVD in females aged <65 years. Rates were higher, and inequalities greater, among males, especially for IHD. For IHD, increased risk for males over females reduced with age (incidence rate ratio for 41–50 year old males=4.28 (95% CI 4.12 to 4.44) and 1.17 (95% CI 1.16 to 1.18) for 71–80 year olds). Inequalities in IHD mortality by area deprivation persisted over time, increasing from around 10% to around 25% higher risk in the most deprived areas between 1974 and 1986 before declining in absolute terms from around 2000. Inequalities for CeVD increased after the late 1980s. Conclusions: IHD and CeVD mortality in Scotland exhibit age but not recent distinct period or cohort effects. The improvements in mortality rates have been more sustained for CeVD and inequalities greater for IHD.